THE EFFECT OF LCP ADDITION TO THE COMPRESSIVE STRENGTH OF NORMAL CONCRETE - Budiman Budiman (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
SNI 03-2847-2002, Concrete is a mixture of portland cement or other hydraulic cements, fine aggregate, coarse aggregate and water. The additives that form solid mass are optional. The aims of this study are to find out the effect of waste nugmet shell (LCP) toward the concrete characteristics, and to determine the compressive strength value of concrete characteristics. Variation of waste nugmet shell (LCP) toward the weight of cement is 0%, 0.25%, 0.50%, and 0.75%. This research is a sample-based laboratory research and analysis of aggregate characteristics and concrete compression test. The research result shows that the waste nugmet shell (LCP) into the concrete mixture affects the compressive strength value of concrete characteristics (fck’). It is proved by the compressive strength value of concrete which increased with the of waste nugmet shell (LCP) 0,25% and LCP 0,50% then decreased after the LCP 0,75%. The increase of fck’ value of the concrete characteristics after LCP 0.25% and LCP 0,50% is equal to 80.03 Kg/cm2 and 86.13 Kg / cm2. It means that there is an increase about 16.34% and 22,26%. The increase of concrete compressive strength value is quite significant if it is compared to non-LCP (normal concrete) with fck’ value about 66,95 Kg/cm2. Meanwhile, the decrease of fck’ value occurs in the proportion of LCP 0.75%, with the value of fck’ obtained t 64.56 Kg/cm2 at the age of 28 days.